Strategi Pendekatan Historis Dan Pragmatis - Dyah Febiyani Nuralifia; Fahrizi Leandro Husaifah; Muhammad Yasin (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract, The practice of implementing education should refer to educational theory and be based on a clear philosophical foundation. In order for educational praxis to be guided by theory, an understanding of educational theory and its philosophical roots becomes important and strategic. Pragmatism believes that the truth or not of a theory depends on whether or not the theory is useful for humans in their livelihoods. This philosophy states that the truth or not of a theory depends on whether or not the theory is useful for humans in their livelihoods. Whether or not a result of thought, proposition or theory is judged according to its usefulness in life or according to the usefulness or not of that theory in human life. Pragmatism is a philosophical reaction to this phenomenon. William James defines pragmatism as "the attitude of turning away from everything, principles, categories, initial necessity, to then move on to everything, results, consequences, and new facts." Pragmatism gives a critical character to old philosophical systems, which, according to pragmatists, have made the mistake of looking for something ultimate, absolute, and eternal essences. Historically, education in a broad sense has been implemented since humans were on this earth. This is in line with human progress in thoughts and ideas about education. According to the Big Indonesian Dictionary, education is defined as the process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training efforts. History cannot be separated from a series of events that have been limited by space and time in which these events were formed and occurred. Many people say that history is something static that cannot possibly be “recycled” based on the context of the era.